Analisis Efektifitas Media Edukasi Booklet Dan E-Booklet Terhadap Perubahan Perilaku Pasien Hipertensi Di Puskesmas Pemulutan Kabupaten Ogan Ilir - Telisa, Imelda; Rahayu, Neneng Endang; Sartono, Sartono (Poltekkes Kemenkes Maluku, 2024)
The incidence of hypertension is increasing every year. Efforts and strategies as well as interventions are needed in efforts to prevent and manage hypertension in the community, especially the age at risk and vulnerable people, so that the increase in cases and severity of hypertension disease can be controlled, one of which is by changing behavior through education. Education carried out with effective media so that it can change behavior in a positive direction in controlling hypertension and its risk factors. The purpose of this study is to determine the effectiveness of Booklet and e-Booklet educational media on improving the knowledge and behavior of hypertension patients at the Pemouthan Health Center. The research was carried out at the Pemouthan Health Center of Ogan Ilir Regency for 1 month. Primary data was collected through respondent demographic questionnaires, interviews in the form of 1 x 24-hour recall and blood pressure level measurement. The type of research used is quantitative research using the Quasi Experiment design. The study used a pre-posttest design with two groups of 45 respondents each with treatment using educational media booklet and educational media e-booklet. The statistical analysis method used is the T-test with the sign Wilcoxon Test. effectiveness test using the N-Gain method. The results of the study showed that there was a significant difference in the knowledge, attitudes and actions of hypertension patients before and after providing education using booklet and e-booklet media. Based on the effectiveness test of educational media, booklets and e-booklets are quite effective in increasing the knowledge of hypertension patients and are not effective against behavior changes.